Symbols and Metaphors: Translations from “Hikayat Inderaputera” into Painting / Mohd Shahrul Hisham Ahmad Tarmizi ...[et al.] - Ahmad Tarmizi, Mohd Shahrul Hisham; Ibrahim, Dr. Marzuki; Mohd Sharif, Mohd Hakim; Muda, Muhammad Shafiq; Mohd Hasan, Adib (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2017)
This research covers constituents of symbols and metaphors based on ‘Hikayat Inderaputera’ and it is connected to the intrinsic and extrinsic elements in visual art. The research is actually related to the view of possibilities of metaphor applied in the study of painting. ‘Hikayat Inderaputera’ can be translated into expressions, imaginations, and perceptions through painting and it also gives meaning and connection in semiotic approach. In a creative process, paintings are always related to narrative as a visual language and it is a part of structure in picture making. To understand metaphors, we need to consider semiotic as a methodology and it requires language as a structure, arguing that structuralism could equally be applied to any system of meaning making. It is actually a set of signal or codes. This research also explains how the researcher remarks and relates ‘Hikayat Inderaputera’ to previous works. In painting, artists always apply metaphors to create visual narratives while they are also being reflected writers. In addition, the researcher realized “Hikayat Inderaputera” as a way of expressions in creating symbols and metaphors. It can be translated into new possibilities of readings, visual languages, signs and can also be developed in new directions to represent other associations in images making especially in painting